Analysis of Hysterectomy Specimens- A histopathological Study - Neetu Punia; Shivani Dua (Asian Journal of Medical Research, 2019)
Background: Hysterectomy means removal of uterus. The present study was conducted to assess histopathology of hysterectomy specimens.Subjects and Methods:The present study was conducted on 104 hystrectomy specimens. The hysterectomy specimens received were immediately transferred into 10% fresh formalin. The histopathological findings of uterus and cervix were then recorded.Results:Clinical indications were ovarian cyst in 2, dermoid cyst in 11, fibroid uterus in 25, menorrhagia in 34, chronic cervicitis in 6, carcinoma cervix in 10, carcinoma endometrium in 7, and uterine polyp in 9. The difference was significant (P< 0.05). Histopathology was normal in 24, adenocarcinoma in 16, leiomyoma in 12, adenomyosis in 16, chronic cervicitis in 20, SCC in 17, endocervical polyp in 7. The difference was significant (P< 0.05).Conclusion: Hystrectomy is a common procedure among females. Histopathology of hysterectomy found to be adenocarcinoma, endocervical polyp leiomyoma, adenomyosis, chronic cervicitis, SCC, and normal histology.